2021
DOI: 10.31219/osf.io/tjyv3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tiềm Năng Phát Triển Năng Lượng Mặt Trời Tại Việt Nam

Abstract: Việc đạt được mục tiêu giảm phát thải khí nhà kính toàn cầu như đã đặt ra trong Thỏa thuận Paris về biến đổi khí hậu sẽ phụ thuộc nhiều vào lộ trình phát triển của các nền kinh tế đang phát triển như Việt Nam. Năng lượng tái tạo là các dạng năng lượng thu được từ môi trường tự nhiên hoặc từ các nguồn có thể được bổ sung một cách tự nhiên, và trong số các năng lượng ta thấy được nguồn năng lượng mặt trời tiềm năng có thể phát triển xa hơn ở Việt Nam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…Given its strategic position, the Central Highlands are in a prime position to enhance exchanges and economic growth, particularly in the development of tourism, with numerous regions in the nation and abroad. Several major tourist routes, such as the Central Heritage Road, the Highland Green Road, and the Trans-Asian Tourist Route, which links Vietnam to Indochina, have been developed (Diep Anh, 2022). The Central Highlands is an underdeveloped region with a substantial percentage (over 30%) of ethnic minority communities, a number of impoverished communes, and an abundance of potential for tourism stemming from its cultural and natural attractions.…”
Section: Central Highlands Research Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Given its strategic position, the Central Highlands are in a prime position to enhance exchanges and economic growth, particularly in the development of tourism, with numerous regions in the nation and abroad. Several major tourist routes, such as the Central Heritage Road, the Highland Green Road, and the Trans-Asian Tourist Route, which links Vietnam to Indochina, have been developed (Diep Anh, 2022). The Central Highlands is an underdeveloped region with a substantial percentage (over 30%) of ethnic minority communities, a number of impoverished communes, and an abundance of potential for tourism stemming from its cultural and natural attractions.…”
Section: Central Highlands Research Areamentioning
confidence: 99%
“…One could say that the Central Highlands' stakeholders haven't been able to work together and coordinate well enough on the tourism story. Expert analysis has revealed that various factors have hindered the development of tourism in the Central Highlands, including a lack of a cohesive job market, inadequate product innovation, and a lack of inter-provincial cooperation (Diep Anh, 2022). Moreover, marketing efforts in the region have not been successful in conveying the significance of the Central Highlands as a tourist destination.…”
Section: Central Highlands Research Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Tuy nhiên, theo Jaiswal và Kant (2018), nhiên liệu hóa thạch được dùng để sản xuất năng lượng không thể tái tạo ngày càng khan hiếm và trong tình hình này, năng lượng mặt trời có thể là giải pháp tốt nhất để đáp ứng cả hai đầu cung và cầu. Và, máy nước nóng năng lượng mặt trời (SWH) là một trong những hình thức sử dụng điện mặt trời đang phát triển tại Việt Nam (Huyen Anh, 2021). Việc sử dụng nguồn năng lượng tái tạo này sẽ không gây ô nhiễm môi trường, không khói bụi, không tiếng ồn và an toàn cho người sử dụng, cho tòa nhà công trình.…”
Section: Giới Thiệu Nghiên Cứuunclassified
“…Không chỉ bảo vệ môi trường mà SWH còn rất an toàn, tiết kiệm đáng kể điện năng tiêu thụ cho gia đình. Với một hệ thống cung cấp nước nóng bằng năng lượng mặt trời hoàn chỉnh, có thể tiết kiệm 60 -90% năng lượng so với các loại thiết bị làm nóng nước truyền thống khác nhưng hiện nay vẫn chưa được sử dụng rộng rãi trong các hộ gia đình (Huyen Anh, 2021). Các sản phẩm SWH này chưa có được chỗ đứng bền vững trên thị trường, nguyên do một phần là thông tin sản phẩm chưa được tuyên truyền, quảng bá rộng rãi, và phần khác là chưa được sự chú trọng quan tâm của các nhà tư vấn thiết kế (Le, 2019).…”
Section: Giới Thiệu Nghiên Cứuunclassified